PEMBERDAYAAN IBU-IBU PKK DESA LAUT DENDANG KECAMATAN PERCUT SEI TUAN DALAM MENGELOLA MANAJEMEN KEUANGAN RUMAH TANGGA KELUARGA SEJAHTERA - Fauziah Rahman; Indah Cahya Sagala; Kharunnisah Lubis (LEMBAGA KAJIAN ILMU SOSIAL DAN POLITIK (LKISPOL), 2021)
This community service was carried out in Laut Dendang village with community service partners, PKK women. This PKM is carried out using classical methods and training or practical methods, namely in the form of short training on household financial management and investment using the financial management module. The purpose of this service activity is to add insight, especially in the morning PKK women in Laut Dendang Village regarding effective and efficient financial financial management as well as forming awareness, mindset and constructive lifestyle patterns, especially in terms of utilizing family income, and being able to use it according to the allocation. and allocation based on a priority scale while increasing the insight and ability of PKK women in Laut Dendang Village in managing household finances to shape the family's future for the better